Living with Art: Repositioning the late works of Thomas Bernhard - Spring, B (2020)
This study re-evaluates and repositions the late writings of the Austrian author Thomas Bernhard (1931-89). Over thirty years after his death, Bernhard is widely considered to be a writer of international relevance. He is renowned for his bleak portrayals of modern society, his scandalous critiques of his homeland, and his infectious and much-imitated linguistic style. But there is another side to Bernhard—one which existing analyses of his domestic controversies and foreign fanbases are yet to examine fully. In this study, I argue that Bernhard’s late prose and dramatic works are centrally concerned with the relationship between art and social living. He explores forms of learning from art, and how engaging with art can affect ways of behaving towards others and oneself.